Motivation in reading for the development of creativity in elementary school children - Cedeño Salavarria, Dania Elizabeth; Jama Zambrano, Víctor Reinaldo (Revista Universidad de Guayaquil, 2023)
Reading is an insurmountable source to acquire new knowledge, its incessant decline has given rise to the elaboration of this study; whose problem is evident in the lack of interest in reading and the poor development of the reading process, due to factors such as lack of motivation to read, few applications of reading techniques and strategies by teachers, and the limited contribution of teachers. parents, therefore the objective of the study is to investigate the importance of motivation in reading for the development of creativity in the students of the elementary school of the School of Basic Education "Enrique Delgado Coppiano" of the Chone canton in the year 2022; The methodology applied was a quantitative approach, the type of study was bibliographic and field, being descriptive, using the inductive-deductive and analytical-synthetic method, with the support of techniques such as interview and test. The results of the study are evidenced in the sample group, concluding the following: the students are motivated by reading; however, the teachers do not know techniques and strategies to promote the motivation and creativity of the students, regarding the assessment of the last element mentioned. boys and girls have better verbal than figurative capacity.
Keywords: Motivation; Reading; Creativity; Learning